2016
DOI: 10.5248/131.467
|View full text |Cite
|
Sign up to set email alerts
|

Four new morel (Morchella) species in the elata subclade (M. sect. Distantes) from Turkey

Abstract: Four Turkish Morchella species identified in published multilocus molecular phylogenetic analyses are described here as new, using detailed macro- and microscopic data: M. mediterraneensis (Mel-27), M. fekeensis (Mel-28), M. magnispora (Mel-29), and M. conifericola (Mel-32). A distribution map of morels identified to date in Turkey is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Turkey has suitable ecological conditions to enable macrofungi biodiversity and more than 2200 macrofungi species have been reported (Sesli and Denchev, 2008;Doğan and Kurt, 2016;Taşkın et al, 2016;Allı et al, 2017;Akata et al, 2018;Doğan et al, 2018;Sesli and Liimatainen, 2018). Among the rich macrofungi biodiversity, 54 Tricholoma taxa (except for T. ilkkae) were reported from Turkey to date and 14 of them are distributed in the Aegean region (Sesli and Denchev, 2008;Şen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Turkey has suitable ecological conditions to enable macrofungi biodiversity and more than 2200 macrofungi species have been reported (Sesli and Denchev, 2008;Doğan and Kurt, 2016;Taşkın et al, 2016;Allı et al, 2017;Akata et al, 2018;Doğan et al, 2018;Sesli and Liimatainen, 2018). Among the rich macrofungi biodiversity, 54 Tricholoma taxa (except for T. ilkkae) were reported from Turkey to date and 14 of them are distributed in the Aegean region (Sesli and Denchev, 2008;Şen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of field and laboratory studies, the samples were identified as Mycena ustalis Aronsen & Maas Geest. The current checklists (Sesli and Denchev, 2014;Solak et al, 2015) on Turkish mycobiota and the contributions made after the checklists (Uzun et al, 2015;Akata et al, 2016;Işık et al, 2016;Sesli et al, 2016;Taşkın et al, 2016;Türkekul and Işık, 2016;Çöl et al, 2017;Demirel et al, 2017;Kaşık et al, 2017;Uzun et al, 2017;Alkan et al, 2018;Kaya and Uzun, 2018;Kaygusuz et al, 2018), revealed that M. ustalis has not been reported from Turkey before.…”
Section: Introductionmentioning
confidence: 99%
“…The number of these investigations have been increased especially for the last decade and the collected data were presented as checklists by different research groups (Doğan et al, 2005;Sesli and Denchev, 2008). Recently, some new contributions were also added to list from different part of Turkey (Acar et al, 2015;Akata, 2017;Akata and Doğan, 2015;Akata and Uzun, 2017;Akata et al, , 2016a2016b;Akçay and Uzun, 2016;Alkan et al, 2016;Allı et al, 2016;Demirel and Koçak, 2016;Doğan and Akata, 2015;Doğan and Kurt, 2016;Dülger and Akata, 2016;Kaya et al, 2016;Topçu Sesli, 2016, 2017;Sesli and Vizzini, 2017;Öztürk C. et al, 2017;Öztürk Ö. et al, 2016;Taşkın et al, 2016;Vizzini et al, 2016;Uzun et al, 2017). The taxonomic investigations around the study area are conducted by Akata (2017); Allı et al (2016), Karamanoğlu and Öder (1973), Solak and Gücin (1992), but there is not any report of mycological investigation in Yalova province.…”
Section: Introductionmentioning
confidence: 99%